Management of hepatic hydatidosis by laparoscopic approach in rural central India: a 3 year experience - Jauhari, Abhinav; Golhar, K.B. (International Journal of Research in Medical Sciences, 2017)
Background: Hydatid disease is still a major health problem in the infested areas of world, mainly in sheep-raising areas. But owing to increased travel and tourism all over the world, it can be found anywhere, even in developed countries.1 Thus, surgeons in nonendemic areas encounter the disease and should be aware of its optimum treatment. A safe, new method of laparoscopic management of hepatic hydatidosis is described along with the review of relevant literature. Methods: From April 2011 to October 2013, Fifteen cases of hepatic hydatid disease were operated on laparoscopically using the Palanivelu hydatid system. Results: The majority of the patients presented in the 4th decade (43.3%) with female sex predisposition (70% females). Most common presenting feature was pain the in upper abdomen. Most of the patients had only a single cyst (76.6%). The right lobe of the liver was most commonly involved. Cysts were bilateral in 6 patients. In all the patients simple evacuation of the hydatid cyst by the palanivelu hydatid system was done. The remnant cavity was dealt with by omentoplasty. The average follow-up period is 6 months. There have been no recurrences to date. Conclusions: Minimal invasive management, using Palanivelu hydatid system for aspiration and laparoscopic intervention, is an alternative to open surgery because of its ability to prevent spillage and thus minimize recurrences.